White Matter Damage in 4,725 Term-Born Infants Is Determined by Head Circumference at Birth: The Missing Link - Arne Jensen; Bert Holmer (Obstetrics and Gynecology International)
Background. White matter damage (WMD) is a prime risk factor for cerebral palsy, in part occurring unexplained. Though primarily a problem of preterm infants, there is growing evidence that in large newborns cephalopelvic disproportion and prolonged labor are involved. Objective. To explore both incidence of and morphometric risk factors for WMD in term-born infants. Study Design. We related growth variables and risk factors of term-born infants to WMD (61/4,725) using odds ratios of z-score bands. Results. The key result is the novel observation that head circumference is a prime and unique index for WMD in term-born neonates over the whole range of centiles (U-shaped; WMD (%) = 3.1168–0.12797∗HC (centile) + 0.0014741∗HC2; p<0.0001). This suggests different mechanisms for WMD in the lowest and highest z-score band. In the latter, cephalic pressure gradients and prolonged labor with preserved neonatal vitality prevail, whereas in the previous one, acute and chronic oxygen deprivation with reduced vitality predominate. Conclusions. The fact that seemingly healthy term-born neonates are not screened by head imaging, in spite of both large head circumference and prolonged labor, is considered to be the missing link between the insult that escapes diagnosis and the development of unexplained developmental delay and cerebral palsy in childhood.